Bioactivity Guided Antidiabetic Formulation Development of Tridax procumbens Linn Leaves - Bansode, Pranali Vijay; Patil, Kiran Shivaji; Hajare, Ashok Ananda (Indian Journal of Pharmaceutical Education and Research, 2020)
Purpose: Diabetes mellitus is a global health problem as it is one of the complex disease and main causes of premature illness and death. The present study was focused to scientifically overcome bioavailability drawbacks of Tridax procumbens Linn. and improve its medicinal use of for the treatment diabetes by formulating it into microemulsion from. In this study oil in water microemulsion of Tridax procumbens Linn leaves extract was prepared using olive oil, Tween 80 and propylene glycol for oral delivery. Methods: Phytochemical screening of Tridax procumbens Linn. leaves extract was carried out to isolate flavonoids by column chromatography. The o/w microemulsion of whole extract was prepared by water titration method followed by its evaluation for various physical tests and thermodynamic stability. The optimized formulation was tested for drug release in vitro and antidiabetic activity by in vivo study. Results: Tridax procumbens Linn. leaves extract isolated for the active moiety showed antidiabetic action in rats. The optimized Tridax procumbens Linn. extract microemulsion showed an average particle size 292.4 nm. There was approximately 1.4 fold increase in drug release from microemulsion compared to marketed tablet formulation. At the end of seven days after oral administration of microemulsion a significant reduction in blood glucose level was observed. Conclusion: The optimized microemulsion was thermodynamically stable. The enhanced bioavailability of flavonoids in microemulsion proves the traditional claim with regard to Tridax procumbens Linn. for its antidiabetic activity.
Keywords: Tridax procumbens; Microemulsion; Alloxan-induced diabetes; Hypoglycemic; activity; Bioavailability